Swarm-Intelligence-Based Optimal Planning of Distributed Generators in Distribution Network for Minimizing Energy Loss. Issue 6 (3rd April 2017) - Kumawat, Manoj; Gupta, Nitin; Jain, Naveen; Bansal, Ramesh C.
Abstract: This research work proposes a heuristic approach for the planning of Distributed Generator (DG) to minimize annual system energy loss. The particle-swarm-optimization-based method has been used as an optimization tool for determining the optimal size and allocating the DGs to minimize energy loss. In this approach, time-varying characteristics of electrical load demand have been considered to mimic real load scenario in the electrical distribution system. The proposed approach is generic and simple. It can provide optimal solutions to the distribution utilities to select multiple DGs in stages under various constraints. The effectiveness of the proposed approach is validated on 16-, 33-, and 69-bus radial distribution networks. The results are compared with those of already existing methods as suggested in the literature.